2021
DOI: 10.3390/cancers13092087
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Drug Use and the Risk of Ovarian Cancer Death among Finnish Ovarian Cancer Patients—A Nationwide Cohort Study

Abstract: Ovarian cancer (OC) has a poor prognosis. Hypertension may be a prognostic factor for OC, but it is unclear whether antihypertensive (anti-HT) drug use of modifies OC prognosis. We performed a population-based analysis assessing the effect of anti-HT drug use on OC mortality. A cohort of 12,122 women identified from the Finnish Cancer Registry with OC in 1995–2013 was combined with information on their anti-HT drug use during the same time period. Use of each anti-HT drug was analysed as a time-dependent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
(32 reference statements)
3
7
0
Order By: Relevance
“…Our result that ACE inhibitors use after ovarian cancer diagnosis is associated with reduced cancer-specific mortality risk is in agreement with results of previous studies [ 6 8 ]. Huang et al (2021), observed a reduced mortality for post-diagnostic therapy involving ACE inhibitors (HR 0.53, 95% CI: 0.31– 0.91), but no association for post-diagnostic use of other antihypertensive medication [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our result that ACE inhibitors use after ovarian cancer diagnosis is associated with reduced cancer-specific mortality risk is in agreement with results of previous studies [ 6 8 ]. Huang et al (2021), observed a reduced mortality for post-diagnostic therapy involving ACE inhibitors (HR 0.53, 95% CI: 0.31– 0.91), but no association for post-diagnostic use of other antihypertensive medication [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Huang et al (2021), observed a reduced mortality for post-diagnostic therapy involving ACE inhibitors (HR 0.53, 95% CI: 0.31– 0.91), but no association for post-diagnostic use of other antihypertensive medication [ 7 ]. Similarly, Santala et al reported, that only ACE inhibitors are associated with improved long term ovarian cancer survival when the effect of cardiovascular mortality is taken into account (HR 0.73 95% CI: 0.58–0.91) [ 6 ]. In a study by Harding et al, ovarian cancer-specific mortality was found to be lower among women who used ACE inhibitors (HR 0.76, 95% CI: 0.63–0.92) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations